Interpopulation Heterogeneity of Deschampsia antarctica Desv According to the Variability of Nuclei Areas and Relative Level of DNA in Different Tissues of Leaves - Parnikoza, I.; Myryuta, N.; Masur, M.; Maidanyuk, D.; Kozerezka, I. (Український антарктичний журнал, 2005)
The objective of the present work was to analyze diversity in several sub-Antarctic populations studying the morphological variability of the average nucleus area in the D. antarctica leaf epidermis and palisade parenchyma and to assess the ability for polysomaty in these tissues. The investigated material gathered on 5 islands of sub-Antarctica: Petermann, Berthelot, Galindez, Rasmussen and Yalour, thus the populations experienced quit different conditions. Целью этого исследования было изучение наличия полисоматии в тканях листа D. antarctica, а также анализ межпопуляционной изменчивости по величине средней площади ядра и относительного содержания ДНК в ядрах клеток эпидермальной и паренхимной тканей листка D. antarctica. В исследовании использовали материал, собранный в марте 2005 г. на пяти островах Субантарктики: Петерман, Бертелот, Галиндез, Расмуссен и Ялур. Метою цього дослідження було вивчити наявність полісоматії в тканинах листка D. antarctica, а також проаналізувати міжпопуляційну мінливість за величиною середньої площі ядра та відносного вмісту ДНК в ядрі клітин епідермальної та паренхімної тканин листка цієї рослини. В дослідженні використовували матеріал, зібраний в березні 2005 р. на п’ятьох островах Субантарктики: Петерман, Бертелот, Галіндез, Расмуссен та Ялур